2004
DOI: 10.1002/chin.200437119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cycloalkanoindoles by an Unusual DAST‐Triggered Rearrangement Reaction.

Abstract: Reaction. -Treatment of symmetrical and unsymmetrical bisindolyl derivatives with DAST results in formation of cycloalkanoindoles which are of biological interest. Surprisingly, irrespective of the substitution pattern the same mixture of products is obtained. Possible mechanism is discussed. -(GIANNINI*, G.; MARZI, M.; MORETTI, G. P.; PENCO, S.; TINTI, M. O.; PESCI, S.; LAZZARO, F.; DE ANGELIS, F.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…During the past decade a large number of natural products containing bis(indolyl)methanes [ 9 ] and bis(indolyl)ethanes [ 10 ] have been isolated from marine sources. Consequently, a number of synthetic methods for the preparation of bis(indolyl)alkane derivatives by reacting indoles with various aldehydes and ketones in the presence of either a Lewis acid [ 11 ] or a protic acid [ 12 , 13 , 14 ], metal salts, such as In(OTf) 3 [ 15 ], Dy(OTf) 3 [ 16 , 17 ], Ln(OTf) 3 [ 18 ], and CeCl 3 ·7H 2 O [ 19 , 20 ], and molecular iodine [ 21 , 22 ], as well as solid acidic catalysts [ 23 , 24 , 25 ], such as clays and Zeolites, have been reported in the literature. In addition, it has been reported that the reactions of indoles with various aldehydes were carried out in a protic solvent in the absence of any other catalyst to afford bis(indolyl)methanes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade a large number of natural products containing bis(indolyl)methanes [ 9 ] and bis(indolyl)ethanes [ 10 ] have been isolated from marine sources. Consequently, a number of synthetic methods for the preparation of bis(indolyl)alkane derivatives by reacting indoles with various aldehydes and ketones in the presence of either a Lewis acid [ 11 ] or a protic acid [ 12 , 13 , 14 ], metal salts, such as In(OTf) 3 [ 15 ], Dy(OTf) 3 [ 16 , 17 ], Ln(OTf) 3 [ 18 ], and CeCl 3 ·7H 2 O [ 19 , 20 ], and molecular iodine [ 21 , 22 ], as well as solid acidic catalysts [ 23 , 24 , 25 ], such as clays and Zeolites, have been reported in the literature. In addition, it has been reported that the reactions of indoles with various aldehydes were carried out in a protic solvent in the absence of any other catalyst to afford bis(indolyl)methanes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These actions depend on an autolysis product of 3-indolylmethyl glucosinolate (glucobrassicin), namely indole-3-carbinol ( I3C , Figure 1 ) [ 4 , 5 ], and the resulting indole oligomers produced in the acidic environment of the stomach: 3,3’-diindolylmethane ( DIM ) [ 4 , 5 ], indolo[3,2- b ]carbazole ( ICZ ) [ 6 , 7 ], the linear trimer LTr [ 6 , 8 , 9 ], the cyclic trimer CTr [ 6 , 8 , 10 ], and the cyclic tetramer CTet [ 11 , 12 ] ( Figure 1 ) [ 2 ]. The current interest of pharmacologists and medicinal chemists in this topic has resulted in several reports which disclosed synthetic analogues of I3C [ 13 , 14 , 15 ], DIM [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and CTr [ 32 ] possessing anticancer properties.…”
Section: Introductionmentioning
confidence: 99%